El expendedor de plantas de la ciudad de medellín : su caracterización social y su saber en salud bucal (2007)
ABSTRACT: The present study allows the characterization of the salesperson as a carrier of knowledge and an ancestral culture, and the permanence in the time. The description of its knowledge is given through classification and systematizing of each one of the plants recommended by them, according to its use in oral cavity; the description of its botanical characteristics and their use; and also the reference of the potential medicinal scientific value of such plants. Methods: a qualitative ethnic study was carried out allowing to comprehend the phenomenon with the purpose of describing an empiric practice settled in a social group, the medical plant salespersons in the city of Medellin. Results: it can be stated that: the salespersons of Medellín constitute a figure placed in a traditional medical system, who possesses internal coherence for the context, due to their role and identified elements in their knowledge, such as: acquisition, transmission and exercise, making up the corpus and praxis of the traditional medical systems as medical chief. Conclusions: the transmission of knowledge is a legacy among generations, in their condition as a “gift” given by human nature. Their practice is close to the shopping centers of the modern city, at the farmers markets, and the new sectors of the informal employment: avenues, streets and boulevards. The salespersons interacts with different sectors, their knowledge is framed within a general logic of syncretism product of their concepts on oral Health.